60 likes | 142 Views
Aim: How do we factor complex base and using regrouping. Do Now: Factor the following 1. 5 x 2 y – 10 xy 2. 2. x 2 – 5 x + 6. 3. x ( y – 1) + 3( y – 1). The GCF can be a monomial or a binomial. x ( y – 1) + 3( y – 1). The GCF is y – 1.
E N D
Aim: How do we factor complex base and using regrouping Do Now: Factor the following 1. 5x2y – 10xy2 2. x2 – 5x + 6 3. x(y – 1) + 3(y – 1)
The GCF can be a monomial or a binomial x(y – 1) + 3(y – 1) The GCF is y – 1 Factor y– 1, then write the remaining in another parenthesis = (y – 1)(x + 3) x2(y + 2) – (y + 2) = (y + 2)(x2 – 1) Factor y+ 2 = (y + 2)(x – 1)(x + 1) Factor (x2 – 1) again
Factor: 2(5x + 2)2 – 7(5x + 2) Factor the GCF (5x + 2) =(5x + 2)[2(5x + 2) – 7] Simplify the expression in the bracket =(5x + 2)(10x + 4 – 7) =(5x + 2)(10x – 3)
Factoring Expressions With Complex Bases (a + 2)2 + 3(a + 2) + 2 Let A = (a + 2). A2 + 3A + 2 Replace (a + 2) with A. = (A + 2)(A + 1) Factor the trinomial. = [(a + 2) + 2] [(a + 2) + 1] Replace (a + 2) with A. = (a + 4)(a + 3) Simplify.
Factor by grouping Group into two binomials Factor by GFC if possible Factor by GFC Factor completely
You Try It Factor each trinomial if possible. • 1)y(x – 2) + 3(x– 2) • 2) x2– x– xy+ y • 3) 5(2x – 3)2 + 9(2x – 3) • 4) (x – 3)2 – 6(x – 3) + 8 • 5) x3 + 3x2 – x – 3